Comparison of Functional Vision and Eye-Related Quality of Life between Myopic Children Treated with Orthokeratology and Single-Vision Spectacles in Southern China - Tingting Yang; Rongsheng Hu; Wen Tian; Ying Lin; Yamei Lu; Xiaolin Liang; Danying Zheng; Xinyu Zhang (Journal of Ophthalmology)
Objective. To compare eye-related quality of life between Chinese children wearing orthokeratology (OK) contact lenses and single-vision spectacles (SVS) using the Pediatric Eye Questionnaire (PedEyeQ) and to evaluate the impact of different myopia correction methods on children and their parents. Methods. Children aged 12–17 years and their parents/legal guardians were recruited. The children’s myopia ranged from −0.50 to −5.00 diopters (D), and their astigmatism was <1.50 D. They had all been wearing OK contact lenses or SVS for at least 12 months. The children completed the Child PedEyeQ. One of their parents (or a legal guardian) completed the Proxy PedEyeQ and the Parent PedEyeQ. Rasch-calibrated PedEyeQ scores were calculated for each domain and were converted to a scale from 0 to 100 for statistical analysis. Results. A total of 50 children wearing OK contact lenses, 43 children wearing SVS, and their parents/legal guardians completed the questionnaires. The scores of all Child, Proxy, and Parent PedEyeQ domains in the OK contact lens group were higher than those in the SVS group (all P<0.05). In the mild and moderate myopia subgroups, the Child, Proxy, and Parent PedEyeQ scores in the mild myopia OK contact lens subgroup were higher than those in the mild myopia SVS group (all P<0.05) except functional vision and bothered by eyes/vision domains for the proxy PedEyeQ. Similarly, the Child, Proxy, and Parent PedEyeQ scores in the moderate myopia OK contact lens subgroup were higher than those in the moderate myopia SVS subgroup (all P<0.05) except impact on parent and family domain for the parent PedEyeQ. In the subgroup analysis of glasses type, no significant score difference of any Child, Proxy, and Parent PedEyeQ domain was detected between mild and moderate myopia in either the OK contact lens group or the SVS group (all P>0.05). Conclusion. Compared with children wearing SVS, children wearing OK contact lenses have better functional vision and eye-related quality of life. Moreover, OK contact lens has a better correction effect, higher acceptance rates, and less impact on parents and families than SVS.